(−)‐β‐Pinene‐based π‐Allylpalladium Complex‐Catalyzed Asymmetric Allylation of Bis‐Imines. Issue 27 (20th July 2020) - Fernandes, Rodney A.; Nallasivam, Jothi L.
Abstract: (−)‐β‐Pinene‐based η 3 ‐π‐allylpalladium complex has shown the efficacy in the catalytic asymmetric allylation of para ‐ and meta ‐xylene spaced bis‐arylimines. The complex has catalyzed asymmetric allylation of various bis‐imines in the presence of allyltributylstannane and two equivalents of water to furnish chiral bis‐homoallylamines in moderate to good yields (up to 70%) and enantioselectivities up to 98.6 : 1.4 er. Abstract : (‐)‐β‐Pinene‐based chiral π‐allylpalladium complex catalyzed the asymmetric allylation of para ‐ and meta ‐xylene spaced C2 ‐symmetric bis‐imines to ( R, R )‐bis‐homoallylamines in enantioselectivities up to 98.6 : 1.4 er